Green bond underdevelopment in Emerging Economies: Exploring the dynamic roles of institutional quality - Epor, Simon Okaja (Universitas Islam Indonesia, 2025)
The underdevelopment of the green bond market in emerging markets is a thing of silent yet unventilated concern among experts and policymakers. Our study identified institutional quality as one of the fundamental determinants of financial development, and so we decided to impose these factors in a green bond situation. Thus, our study consider to examine the influences of institutional quality in explaining green bond development in twenty-one (21) emerging economies from 2010 to 2023. Due to data availability factor and nature of data, the most suitable technique is the panel Fully Modified Ordinary Least Squares (PFMOLS) estimator. The proxy for the institutional quality data is regulatory quality, voice and accountability, and rule of law as well as their PCA estimation. The main findings of the study include that comprehensive institutional qualities are more beneficial to green bond development in emerging economies than isolated institutional quality components. Also, that policy efforts in emerging economies that pursue comprehensive institutional quality will be more beneficial to green bond development in emerging economies if the detrimental influences of trade openness, exchange rate stability, savings are addressed. The study recommends for more institutional reforms in emerging economies to be associated with improvement in savings, financial development, exchange rate stability and trade openness necessary for developing the green bond market.